PELATIHAN DIGITAL MARKETING DENGAN MENGGUNAKAN TIKTOK BAGI MASYARAKAT DI KOTA SIDOARJO - Sholikha Oktavi Khalifaturofi'ah; Dewi Ayu Wulandari; Zufra Inayah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Technological developments bring changes in several fields. One of them is marketing. Marketing that used to be done personally, is now starting to develop online. Online marketing is one of the important things to market products. The most widely used use of digital marketing is using TikTok. TikTok is one of the applications with the most number of downloads in 2021. A total of 656 million downloads for the TikTok application. This cyber training activity aims to train people, especially people in the city of Sidoarjo, to be literate in digital marketing. The participants of this cyber training activity were 44 people. The result of this cyber training is that people are more familiar with the TikTok application and how to use it to market their products. In addition, people are more enthusiastic about developing their business because it is easier to reach customers and take advantage of the TikTok application. Through sources who are experts in this field, participants want additional.